Meningkatkan Kemampuan Berbicara Siswa Kelas 1 Melalui Model Pembelajaran NHT di Sekolah Dasar - Salsabila, Talia; Adikara, Fahmi Surya; Nurani, Dwi Cahaya; Sumarni, Sumarni (Jurnal Didaktika Pendidikan Dasar, 2025)
The implementation of the Numbered Head Together (NHT) learning model was carried out because the observation results showed that the speaking ability of grade 1 students at SDN 11 Indralaya had not yet reached the Minimum Completion Criteria (KKM). The use of the NHT model aims to improve the speaking ability of grade 1 students at SDN 11 Indralaya on the Indonesian Picture Story material. This research is a Classroom Action Research (CAR) model Kemmis and McTaggart, in 2 cycles. Each cycle consists of four stages, namely: planning, action, observation, and reflection. The subjects of this study consisted of 26 students. The results showed an increase in the success target from cycle I by 65.7% to 85.7% in cycle II. It can be concluded that the application of the NHT model can improve students’ speaking ability.